Expatriate assignment : the Singapore experience - Gan, Chee Hiong (2014)
Research on recent graduates and final-year undergraduates of Nanyang Technological University revealed that career prospects and the components of the compensation package were critical factors they would consider before accepting an overseas assignment. More than three quarters of these potential Singapore expatriate surveyed expect to be paid two times more than their counterparts who would rather work in Singapore. Housing, medical and transport allowances were cited as very important components in the remuneration package. This high expectation could lead to an expectation gap between these potential expatriates and their employers .